Use of ultrasonography for fetal circulation assessment in canine pregnancy: A review - Maíra Planzo Fernandes; Gleice Mendes Xavier; Miguel Ferreira Bomfim Baptista; Marcus Vinícius Galvão Loiola; Antonio de Lisboa Ribeiro Filho (Revista Brasileira de Saúde e Produção Animal)
ABSTRACT This literature review discusses advances in gestational ultrasound in bitches, focusing on the use of Doppler technology for maternal-fetal hemodynamic assessment. Ultrasound is an essential tool in veterinary obstetrics, enabling early pregnancy detection, monitoring of embryonic and fetal development, and predicting the due date. B-mode imaging allows for the visualization of fetuses and their structures but has limitations in vascular assessment. Therefore, the use of Doppler, especially Triplex Doppler (B-mode, color Doppler, and pulsed Doppler), is crucial for a detailed evaluation of maternal-fetal blood flow. Monitoring Doppler indices, such as the Resistive Index (RI) and Pulsatility Index (PI), is critical in detecting changes in umbilical and placental circulation, which can predict issues like intrauterine growth restriction and fetal distress. These findings aid in predicting delivery time and identifying fetuses at risk. The objective of this review is to highlight the importance of Doppler ultrasonography as a non-invasive and effective method to improve clinical decision-making and reproductive outcomes, reinforcing its relevance in current veterinary practice.